Logoterapi untuk Meningkatkan Meaning in Life pada Narapidana Penyalahgunaan Narkotika - Ida Bagus Gde Agung Yoga Pramana; Ika Yuniar Cahyanti; I Gusti Ayu Diah Fridari (Universitas Kristen Maranatha, 2021)
Prisoners are one of the vulnerable groups who experience psychological problems. Conditions in prisons, limited activities, and deprivation of freedom give rise to psychological problems in prisons, which affect the low meaning of life. The low meaning of life can lead to erroneous meaning for prisoners of drug abuse. Prisoners can think that drug use and drug addiction behavior are the only positive aspects of their lives. The purpose of providing Logotherapy intervention with the Meaning-Centered Psychotherapy technique for prisoners of narcotics abuse in Prison “X” is to increase the meaning of life in prisoners, which is done by inviting inmates to determine the meaning of life through sources of meaning life. The method used in this study is a quantitative method supported by qualitative data derived from observations and interviews. The results showed an effect of giving Logotherapy intervention on the level of meaningfulness of life in the subject. Keywords: Logotherapy, meaning in life, narcotics prisoners